A case of gastrocnemius muscle with three heads - Üzel, Mehmet; Soyluoğlu, Ali İhsan; Tanyeli, Ercan; Kahraman, Güler; Vural, Feridun (Cerrahpaşa Medical Journal, 2014)
During the routine dissection in our department in 2007–2008, we observed that the right gastrocnemius muscle consisted of three heads in a 56-year-old male cadaver. The third head originated from the posterior surface of the lateral condyle of the femur and joined to the medial head. Tibial nerve and popliteal vessels passed between the third and the medial heads. The literature was investigated. The soleus, plantaris and popliteus muscles were normal. This kind of anatomical variations, which can cause neurovascular entrapment symptoms, should be kept in mind during the differential diagnosis of the complaints at the popliteal region.